Atividade física como moderadora e mediadora na associação entre problemas de sono e sintomas depressivos em estudantes universitários da américa latina: uma análise transversal da coorte UNILIFE-M - Santos, Eduarda Bitencourt dos (2025)
Introduction: University students are a high-risk population for low levels of physical activity (PA), a high prevalence of depressive symptoms (DS), and sleep-related problems (SP). DS and SP are associated; however, there is a lack of studies investigating moderators and mediators of this association, with the limited available literature primarily originating from Global North populations. PA is a protective factor against DS and SP; however, studies exploring the moderating and mediating roles of PA in the relationship between SP and DS among Latin American university students are still lacking. Objective: To investigate the associations between PA, SP, and DS, and the moderating and mediating role of PA in the association between SP and DS in a sample of Latin American university students. Methods: A cross-sectional analysis of the prospective UNILIFE-M cohort. Data were collected through an online survey using the RedCap platform. Students from 24 Latin American universities were invited to participate. PA was assessed using the Short Multidimensional Inventory Lifestyle Evaluation. SP were initially evaluated using the sleep domain of the DSM-5 Level 1 Cross-Cutting Symptom Measure to screen for potential symptoms. Participants who scored ≥2 in this domain were directed to the sleep problems domain of the Pittsburgh Sleep Quality Index (PSQI). A score of ≥10 was used to define the presence of SP symptoms. DS were assessed using two questions from the Patient Health Questionnaire-2 (PHQ-2). Moderation and mediation analyses were conducted using multiple linear regression with SPSS 20.0 and the macro-PROCESS. Results: A total of 8,356 university students were recruited, with a mean age of 20.0±3.4 years, 60.7% of whom were female. The findings revealed a positive association between sleep problems (SP) and depressive symptoms (DS) (Coef=1.107; 95% CI=0.839 to 1.374; p<0.001), a negative association between physical activity (PA) and DS (Coef=-0.132; 95% CI=-0.150 to -0.113; p<0.001), and a lower likelihood of SP among students with healthier lifestyles in the PA domain (OR=0.918; 95% CI=0.895 to 0.941; p<0.001). PA did not moderate the association between SP and DS (Coef=0.025; 95% CI=-0.010 to 0.061; p=0.159). However, PA was found to mediate the association between SP and DS (Coef=1.341; 95% CI=1.248 to 1.434; p<0.001). The direct effect, adjusted for the mediating variable, was 1.287 (95% CI=1.195 to 1.379; p<0.001), while the indirect effect was 0.05 (95% CI=0.037 to 0.071). The mediation proportion was 0.95, indicating partial mediation, with 5% of the effect being mediated. Conclusion: Physical activity does not appear to moderate the association between sleep problems (SP) and depressive symptoms (DS). However, it mediates 5% of this association, suggesting that physical activity serves as a partial mechanism linking SP and DS.